Teaching motion design : course offerings and class projects from the learning undergraduate and graduate programs. - Heller, Steven, 1950-; Dooley, Michael, ....- (New York : Allworth, 2008)
The study of motion design is essential for anyone entering the graphic design industry. Steven Heller and Michael Dooley present the first comprehensive look at course offerings from more than thirty leading design, illustration, animation, and computer art programs. Respected professors from prestigious schools, such as California Institute of the Arts, University of San Francisco, The Ohio State University, School of Visual Arts, Massachusetts College of Art, Rochester Institute of Technology, and many others, offer more than fifty syllabi packed with detailed information and class projects for this up-and-coming area of graphic design. Includes syllabi from courses such as: * Motion Graphics Portfolio * Type in Motion * Introduction to Time-Based Media * 3-D Computer Animation Workshop * Time-Based Communication: Grammar and Syntax * Beginning Character Animation * Sound + Motion * Interactive Media * Film for Graphic Designers * Design for Television: Graphic Design Using Time, Motion, and Sound * The Music Video: A Real World Workshop * Animation Action Analysis * Digital Video * Kinetic Typography * Senior Graphic Communications